Implicit and explicit motor sequence learning in children born very preterm. (January 2017) - Jongbloed-Pereboom, Marjolein; Janssen, Anjo J.W.M.; Steiner, K.; Steenbergen, Bert; Nijhuis-van der Sanden, Maria W.G.
Abstract: Background: Motor skills can be learned explicitly (dependent on working memory (WM)) or implicitly (relatively independent of WM). Children born very preterm (VPT) often have working memory deficits. Explicit learning may be compromised in these children. Aims: This study investigated implicit and explicit motor learning and the role of working memory in VPT children and controls. Methods: Three groups (6–9 years) participated: 20 VPT children with motor problems, 20 VPT children without motor problems, and 20 controls. A nine button sequence was learned implicitly (pressing the lighted button as quickly as possible) and explicitly (discovering the sequence via trial-and-error). Results: Children learned implicitly and explicitly, evidenced by decreased movement duration of the sequence over time. In the explicit condition, children also reduced the number of errors over time. Controls made more errors than VPT children without motor problems. Visual WM had positive effects on both explicit and implicit performance. Conclusion: VPT birth and low motor proficiency did not negatively affect implicit or explicit learning. Visual WM was positively related to both implicit and explicit performance, but did not influence learning curves. These findings question the theoretical difference between implicit and explicit learning and the proposed role of visual WM therein.